Assessing Knowledge, Attitude and Practice among Married Men towards Family Planning in Sarlahi District, Madhesh Province (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Acknowledging a man’s perspective on family planning methods and service is vital for the overall health of the family. A holistic approach involving both partners is key to effective family planning and healthier family life. Therefore, the study aims to find the knowledge, attitude and practice among married men towards family planning at Kabilasa municipality of Sarlahi district.MATERIALS AND METHODS: A cross-sectional descriptive study was carried out Multistage random sampling technique was used for the selection of wards as well as the participants. The total of 164 participants whose wife was in age group (15-49 years) was interviewed. The data was analysis was done by using SPSS 23 version software.RESULTS: Total of 164 participants was interviewed. Higher percent (67.7%) of participants were in age group 30-44 years. almost all (98.2 %) of participant heard about family planning method where meaning of family planning revealed as limiting number of child with higher percentage (88.3%) followed by birth spacing were (81.8 %).96.4% supported the concept of family planning About 98.8% of the participants  expressed that the Spousal communication and decision making are essential for family planning, 84.1% of them stated that family planning is women’s business. Only 27% male had ever used family planning methods though, about 56.7% wives were using Depo as contraceptive.CONCLUSIONS: It can be inferred that a majority of participant possessed knowledge regarding family planning method, highlighting the pervasiveness of information on reproductive health within the surveyed population. However, it perceived as a women’s responsibility, with men often neglecting their role.